Masters of the Narrative: Culture and Power in Global Media’s Take on Palestine-Israel Conflict - Meranti, Meranti; Isa, Danto Erfantoro; Silviana, Isna (Communications, 2024)
The study explores how major international media outlets craft and convey narratives, with a focus on Al Jazeera, BBC, and CNN. Grounded in Edward Said's "Orientalism," the research aims to unveil the cultural nuances and power relations inherent in the portrayal of this longstanding geopolitical conflict. Objectives: Examine Cultural Narratives: Analyze how cultural narratives are constructed and communicated by Al Jazeera, BBC, and CNN in their coverage of the Palestine-Israel conflict. Uncover Power Dynamics: Investigate the manifestation of power relations within editorial decisions and narrative framing by these global media giants. Evaluate Narrative Mastery: Assess the degree to which cultural biases and power dynamics influence the editorial stance of Al Jazeera, BBC, and CNN in the context of the conflict. Methodology: Utilizing a qualitative content analysis approach, this research will scrutinize a diverse sample of articles, videos, and social media content from the chosen outlets. Thematic analysis will be applied to identify recurring cultural themes and power dynamics, allowing for a comparative examination across the media landscape. Key Results: Anticipated findings include insights into how each outlet masterfully constructs cultural narratives, an understanding of power dynamics influencing editorial decisions, and an exploration of how user engagement further shapes the narrative landscape. By unravelling the intricate dynamics of media influence, this study contributes to a nuanced comprehension of the complex interplay between culture and power in global media's representation of the Palestine-Israel conflict.